Выбор точки зрения, картинной плоскости и центра проецирования при визуализации трёхмерной сцены - Ницын, Александр Юрьевич (My University, 2018)
Рассмотрен выбор главных элементов построения перспективы. Приведены доказательства утверждений о том, что для построения перспективы, близкой зрительному восприятию, точка зрения должна находиться в главной точке картины, изображаемый предмет – в пределах угла нормального видения с вершиной в точке зрения, а центр проецирования должен располагаться в точке, удаленной от картинной плоскости на расстояние, вчетверо превышающее высоту точки зрения.

The choice of main elements of construction of perspective is considered. Demonstrations of assertions that for the construction of perspective, closed to the visual perception, a point of view must be in the main point of picture, represented object – within the limits of angle of normal vision with a vertex in the point of view and the center of projection must lie in a point, remote from a picture plane on distance, fourfold exceeding the height of point of view, are furnished. In work three rules of a choice of the main elements of construction of prospect are offered: a rule of a choice of the point of view, a rule of a choice of position of a represented subject in relation to a picture plane and a rule of a choice of distance from the center of displaying up to a picture plane. It is shown, that application of these rules is provided with construction of the prospect closer to visual perception, than the prospect constructed by rules, stated in known works on descriptive geometry.
The choice of view point, picture plane and center of projection for visualization of the threedimensional stage
Keywords: зрительное восприятие; линейная перспектива; главные элементы построения перспективы; точка зрения